The formation of reflective competence in students of technical universities - Sharipova Iroda Azamatovna (Fergana methodical school, 2026)
The article examines the problem of forming reflexive competence in students of technical higher education institutions majoring in Mining and Metallurgy in English language teaching under conditions of educational modernization. The necessity of developing reflection through integrated technologies as a key component of the professional training of future mining and metallurgical engineers is substantiated. The structural components of reflexive competence are disclosed, the pedagogical conditions and complexities of its formation are defined and effective methods and technologies for implementing student self-analysis are analyzed. The results of the experimental work are presented, confirming the effectiveness of the integrated approach in teaching and how the approach influences the formation of students' reflexive competence.